Experimental Evaluation of a Rare Earth-Free Permanent Magnet Generator - Eklund, Petter; Sjolund, Jonathan; Berg, Marcus; Leijon, Mats; Eriksson, Sandra (IEEE transactions on energy conversion, 2021)
Low speed, high torque machines are used in wind turbines where the turbine rotor is directly connected to the generator. A permanent magnet synchronous generator using high-energy rare-earth permanent magnets (PMs) is one common choice for this application, but rare-earth PMs have supply insecurities and cost risks. A rare-earth free 32-pole PM generator, using ferrite PMs in a spoke-type rotor, for use in a 12 kW experimental wind turbine is built and tested. Voltages and currents at load and no load are measured, as well as the magnetic field in the end regions of the machine. The generator can deliver the required power at nominal speed and has low harmonic content in the output. The electrical measurements are compared to two-dimensional finite element design calculations and the experimental results are lower than expected from simulations. The measured voltage is lower than expected, requiring a higher current than calculated for the rated power. Three-dimensional magnetic field simulations show that there are leakage flux paths in the end-regions that the two-dimensional design calculations overlook, explaining the discrepancy between simulations and measurements.